Identification of CNOT1-CCR4-NOT as a suppressor of 53BP1-p53-p21 signaling - Galarreta, Antonio; Pasti, Virginia; Vornberger, Julia; Imhof, Ralph; Oppikofer, Mariano; Altmeyer, Matthias (Cell reports (Cambridge), 2025)
Tumor suppressor p53 has inherent propensities to self-associate, which can lead to oncogenic p53 aggregation. The genome caretaker 53BP1 interacts with p53, forms DNA damage-associated condensates, and has been implicated in p53 activation. Modulating the balance between functional p53 self-association and dysfunctional aggregation may restore tumor-suppressive functions of p53 in cancers with otherwise dampened p53 activity. Here, we identify cellular regulators of 53BP1-p53 signaling based on multi-dimensional high-content microscopy screens using nuclear p53 levels and 53BP1-p53 condensates as primary readouts. Through orthogonal validation, carbon catabolite repression 4 (CCR4)-negative on TATA-less (NOT) transcription complex subunit 1 (CNOT1) emerges as a suppressor of 53BP1-p53-p21 signaling. Consequently, depletion of CNOT1 impairs proliferation, induces apoptosis, and causes cancer cell death. CNOT1 interacts with 53BP1 and impacts its nuclear dynamics, and CNOT1 loss upregulates p53 target gene expression. Finally, we demonstrate that CNOT1 loss suppresses cytoplasmic aggregation of mutant p53, thereby restoring nuclear localization and functionality of p53 mutants frequently found in cancer. [Display omitted] •Multi-dimensional high-content microscopy-based screens for regulators of 53BP1-p53 signaling•Elevated p53 upon depletion of WDR75, DDX24, DDX47, RBMX, SF3A2, and CNOT1 of CCR4-NOT•CCR4-NOT regulates 53BP1-p53 signaling and p53 target gene expression at multiple levels•CNOT1 depletion rescues mutant p53 and increases p21 levels in p53 mutant cancer cells p53 signaling is frequently dampened in cancer. 53BP1 binds p53 and enhances p53 target gene expression. Galarreta et al. identify CNOT1 of the CCR4-NOT complex as a regulator of 53BP1-p53 signaling and show that CNOT1 depletion boosts p53 target gene expression, selectively compromises cancer cell survival, and rescues mutant p53 functions.